Kajian Pola Sebaran Ruko yang Beralih Fungsi menjadi Kos-Kosan di Sekitar Kampus - Vania Dea Wibowo; Muhammar Khamdevi (Prodi Arsitektur Universitas Matana, 2019)
The purpose of this study was to determine the factors that caused the shophouse to switch to a boarding house for the potential elements of the UMN region, to know the pattern of distribution of functions of shophouses to boarding houses around the campus with a case study of boarding houses around UMN, and to find out the factors causing the distribution pattern of shop houses that switch functions to boarding houses with a case study of boarding houses around UMN. Nowadays, the spread of shop houses that change functions into boarding houses, especially around the center of activity. However, if the distribution of shophouses that change functions as a boarding house is not regulated so that it will cause the growth of wild function changes and spread to other areas causing disruption to regional land use. This study takes the title